An Empirical Study on the Powerloom Entrepreneurs Expectations towards the Enhancement of Business Ecosystem with Special Reference to Tamilnadu - Sudha, S.; Nathiya, K.; Thamilchelvam, N.; Jothibasu, L. (International Journal of Psychosocial Rehabilitation, 2019)
The power loom sector is ultimately a labor-focused sector. It offers large-scale employment prospects to the societies there by helping in solving the unemployment problem successfully. The power loom units are usually located in semi-urban and rural zones and support altering the regional inequities. It has empowered the weaker segments of society to earn their livelihood. In the present study, we collected systematically both extensive primary and reliable secondary data. For collecting primary data, convenience sampling technique was used in the study area through a structured questionnaire. The expectation of support from the government for rehabilitating the powerloom industry and the opinion regarding the scope of growth and development in the powerloom sector in the near future, etc., were also collected. The total sample size of 500 respondents was approached in Erode, Karur, and Salem districts. The total populations of the power loom entrepreneurs are not available since more entrepreneurs have not registered themselves with proper authority for doing the power loom business. The non-availability of the total population made the researcher adopt a non-probability sampling method. Under this convenience, sampling techniques were used to collect the primary data.